tính 25.(-1/5)^3+1/5+2.(-1/2)^2-1/2 tìm x, y biết x-1/2=y/3 và x+y=11 07/08/2021 Bởi Everleigh tính 25.(-1/5)^3+1/5+2.(-1/2)^2-1/2 tìm x, y biết x-1/2=y/3 và x+y=11
Đáp án: $a,$ `25 . (-1/5)^3 + 1/5 + 2 . (-1/2)^2 – 1/2` `= 25 . (-1/125) + 1/5 + 2 . 1/4 – 1/2` `= -1/5 + 1/5 + 1/2 – 1/2` `= (-1/5 + 1/5) + (1/2 – 1/2)` `= 0` $b,$ Từ `x + y = 11` `-> y = 11 – x (1)` Ta có : `x – 1/2 = y/3` Thay `(1)` vào ta được : `x – 1/2 = (11 – x)/3` `-> (2x)/2 – 1/2 = (11 – x)/3` `-> (2x – 1)/2 = (11 – x)/3` `-> (2x – 1) . 3 = 2 . (11 – x)` `-> 6x – 3 = 22 – 2x` `-> 6x – 3 – 22 + 2x = 0` `-> (6x + 2x) + (-3 – 22) = 0` `-> 8x – 25 = 0` `-> 8x = 25` `-> x =25/8` Với `x = 25/8` `-> y = 11 – 25/8` `-> y = 63/8` Vậy `x = 25/8, y = 63/8` Bình luận
$25.(-1/5)³+1/5+2.(-1/2)²-1/2$ $=25.(-1/125)+1/5+2.(-1/4)-1/2$ $=-1/5+1/5+(-1/2)-1/2$ $=-1$ b, $x-1/2=y/3$ Thay $x=11-y$ vào phương trình ta được: $11-y-1/2=y/3$ $⇒21/2 -y=y/3$ $⇒63/2 -3y=y$ $⇒4y=63/2$ $⇒y=63/8$ $⇒x=25/8$ $@nguyenduy28364$ Bình luận
Đáp án:
$a,$ `25 . (-1/5)^3 + 1/5 + 2 . (-1/2)^2 – 1/2`
`= 25 . (-1/125) + 1/5 + 2 . 1/4 – 1/2`
`= -1/5 + 1/5 + 1/2 – 1/2`
`= (-1/5 + 1/5) + (1/2 – 1/2)`
`= 0`
$b,$
Từ `x + y = 11`
`-> y = 11 – x (1)`
Ta có : `x – 1/2 = y/3`
Thay `(1)` vào ta được :
`x – 1/2 = (11 – x)/3`
`-> (2x)/2 – 1/2 = (11 – x)/3`
`-> (2x – 1)/2 = (11 – x)/3`
`-> (2x – 1) . 3 = 2 . (11 – x)`
`-> 6x – 3 = 22 – 2x`
`-> 6x – 3 – 22 + 2x = 0`
`-> (6x + 2x) + (-3 – 22) = 0`
`-> 8x – 25 = 0`
`-> 8x = 25`
`-> x =25/8`
Với `x = 25/8`
`-> y = 11 – 25/8`
`-> y = 63/8`
Vậy `x = 25/8, y = 63/8`
$25.(-1/5)³+1/5+2.(-1/2)²-1/2$
$=25.(-1/125)+1/5+2.(-1/4)-1/2$
$=-1/5+1/5+(-1/2)-1/2$
$=-1$
b, $x-1/2=y/3$
Thay $x=11-y$ vào phương trình ta được:
$11-y-1/2=y/3$
$⇒21/2 -y=y/3$
$⇒63/2 -3y=y$
$⇒4y=63/2$
$⇒y=63/8$
$⇒x=25/8$
$@nguyenduy28364$